2018
DOI: 10.1007/s00125-018-4640-0
|View full text |Cite
|
Sign up to set email alerts
|

An adult-based insulin resistance genetic risk score associates with insulin resistance, metabolic traits and altered fat distribution in Danish children and adolescents who are overweight or obese

Abstract: Aims/hypothesisA genetic risk score (GRS) consisting of 53 insulin resistance variants (GRS53) was recently demonstrated to associate with insulin resistance in adults. We speculated that the GRS53 might already associate with insulin resistance during childhood, and we therefore aimed to investigate this in populations of Danish children and adolescents. Furthermore, we aimed to address whether the GRS associates with components of the metabolic syndrome and altered body composition in children and adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Consistently, an obesity GRS predicted the risk of IR in a Chinese children population [37]. Moreover, an adult-based GRS encompassing 53 SNPs was associated with the HOMA-IR index, metabolic syndrome traits, and altered fat distribution in a sample of Danish children and adolescents [38].…”
Section: Discussionmentioning
confidence: 65%
“…Consistently, an obesity GRS predicted the risk of IR in a Chinese children population [37]. Moreover, an adult-based GRS encompassing 53 SNPs was associated with the HOMA-IR index, metabolic syndrome traits, and altered fat distribution in a sample of Danish children and adolescents [38].…”
Section: Discussionmentioning
confidence: 65%
“…A previous study in the TDCOB cohort suggested that there may be differences in genetic influences on body fat distribution between children who are overweight/obese and those who are normal-weight (40). We performed analyses stratified by weight status to test whether the effect of the WHRadjBMI GRS on body fat distribution and cardiometabolic risk is modified by overweight/obesity.…”
Section: Comparing the Results Between The 19 Snp Grs And The Full 48mentioning
confidence: 99%
“…For example, results on 53 loci, in several genes including INSR, IRS1 and PIK3R1 genes, selected based on genome-wide analyses of fasting insulin adjusted for BMI, did not identify loci with a primary effect on higher adiposity and insulin resistance in a large study on adults. 38 However, a genetic score, computed from the same 53 loci, was associated with insulin resistance, in children with overweight or obesity, 45 suggesting that genomic approaches need to be integrative, and also envisaging gene-gene interaction effects. SNPs identified to be associated with NAFLD were not included in the 53 SNPs studied in relation to insulin resistance.…”
Section: Genetic Predictors For Insulin Resistancementioning
confidence: 99%